Pendidikan Karakter Berbasis Etnokonseling di Masyarakat Multikultural - Desi Arpa; Micha Felayati Silalahi (LSM Catimore dan Sahabat Jl. Paya Ilang/Pertamina Desa Lemah Burbana, Takengon, Aceh Tengah 24552, 2026)
Character education in multicultural environments often faces obstacles such as cultural egoism and low levels of tolerance among early childhood students; however, existing counseling approaches remain generic and have not addressed local cultural roots. This study aims to analyze the effectiveness of an ethnocounseling approach in optimizing character formation for early childhood in multicultural settings. Using a descriptive qualitative method, data were collected through participant observation, in-depth interviews, and documentation at Early Childhood Education (PAUD) institutions in heterogeneous regions. The research findings indicate that the integration of local cultural values into the counseling process significantly enhances cross-cultural empathy and self-awareness in children. The originality of this study lies in the formulation of an ethnocounseling model that synergizes indigenous wisdom with modern counseling techniques as a preventive instrument against identity conflicts from an early age. These results imply the importance of a culture-based curriculum in early childhood education in Indonesia